2015
DOI: 10.2341/13-155-l
|View full text |Cite
|
Sign up to set email alerts
|

Localized and Generalized Simulated Wear of Resin Composites

Abstract: A laboratory study was conducted to examine the wear of resin composite materials using both a localized and generalized wear simulation model. Twenty specimens each of seven resin composites (Esthet•X HD [HD], Filtek Supreme Ultra [SU], Herculite Ultra [HU], SonicFill [SF], Tetric EvoCeram Bulk Fill [TB], Venus Diamond [VD], and Z100 Restorative [Z]) were subjected to a wear challenge of 400,000 cycles for both localized and generalized wear in a Leinfelder-Suzuki wear simulator (Alabama machine). The materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Previous studies utilizing the generalized (bulk) wear model have used 400,000 cycles for testing of resin-based materials. [18][19][20][21][22][23] Leinfelder and Suzuki 22 have reported that for resin composite materials, there was a high level of agreement between wear generated with 400,000 cycles in the Alabama simulator and 3 years of clinical service. Over the years, most of the laboratory testing with the Alabama machine has been done using 400,000 cycles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies utilizing the generalized (bulk) wear model have used 400,000 cycles for testing of resin-based materials. [18][19][20][21][22][23] Leinfelder and Suzuki 22 have reported that for resin composite materials, there was a high level of agreement between wear generated with 400,000 cycles in the Alabama simulator and 3 years of clinical service. Over the years, most of the laboratory testing with the Alabama machine has been done using 400,000 cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Barkmeier and others [18][19][20] have conducted several studies with the generalized (bulk) wear model used in this study to evaluate the wear resistance of resin composite materials. The new slit or gap model was used in the present study to more closely parallel a clinical situation in the assessment of wear resistance of self-adhesive resin cements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these methods was the Alabama method, which was developed at the University of Alabama (22). Barkmeier et al (27) have recently developed the simulated localized wear, which was used by Latta et al (23), using a ProScan 2100 non-contact profilometer in conjunction with the AnSur 3D software for wear analysis. In the present study, this method was used to measure the simulated localized wear in the resin luting cements.…”
Section: Discussionmentioning
confidence: 99%